(untitled) (REMUNOM, 2025)
This article shows the practical application of the “ISA” tool - Sustainability Indicator in Agroecosystems, to evaluate the properties participating in the pro-species program in the northeast of Minas Gerais, a territory called Capixaba/Gerais, where the Ministry of the Environment and Climate Change, in collaboration with its linked agencies and partner organizations, developed the “Pro Species: National Strategy for the Conservation of Endangered Species” Project, which seeks to allocate resources to the Program to adopt prevention, conservation, management and administration actions that can minimize threats and the risk of extinction of species. The ISA tool was used as a parameter to obtain an initial diagnosis, draw up plans for improvements, aiming at a rational use of natural resources, for a better understanding of the environment in which they are inserted. For this purpose, the use of indicators, which aim to monitor the socioeconomic and environmental impact resulting from agricultural activities, constitutes an important instrument to subsidize the elaboration and implementation of public policies, programs and projects aimed at the sector and assist producers in the management of their agricultural establishments, such as PASEA (Plan for Adequacy of Agricultural Resources). socioeconomic and environmental) that initiated productive environmental zoning by starting by analyzing the amount of water available and the region’s agricultural production capacity.